Philosophy and Politics in Aristotle’s Politics - Johnson, Curtis N. author. aut Link
XVII, 187 p.
Keywords: Johnson argues that Aristotle's Politics needs to be understood as a 'two-layered' treatise - the first being Aristotle's political theory, and the second as a set of questions for statesmen and politicians. Employing this model, the book sets about to provide a reconceptualization of Politics as a multi-layered, canonical work.